Using Collagen Peptides From the Skin of Monkfish (Lophius litulon) to Ameliorate Kidney Damage in High-Fat Diet Fed Mice by Regulating the Nrf2 Pathway and NLRP3 Signaling - Miao, Bingtao; Zheng, Jiawen; Zheng, Guoping; Tian, Xiaoxiao; Zhang, Wen; Yuan, Falei; Yang, Zuisu (Frontiers in Nutrition, 2022)
Background: Oxidative stress and inflammation play important roles in high-fat diet (HFD) induced kidney damage. Previous studies show that the collagen extracted from the skin of monkfish (Lophius litulon) with pepsin (PSC) exhibits good biological activities. This study investigates the protective effect of PSCP against chronic kidney injury in HFD-fed mice. Methods: PSC was further hydrolyzed into collagen peptides, and the compound with the best DPPH clearance rate was named PSCP. A group of mice was fed an HFD for 4 weeks, and then for another 6 weeks PSCP was added to their diet at the amount of either 100 mg/kg or 200 mg/kg. Results: PSCP treatment (200 mg/kg) reduced the mice’s serum levels of uric acid, creatinine, and blood urea nitrogen by 27%, 20%, and 37%, respectively. This treatment also remarkably improved renal histopathology. Moreover, the activities of superoxide dismutase, glutathione peroxidase, and catalase were increased by 96%, 52% and 74%, respectively, and decreased the malondialdehyde level by 36%. Additionally, PSCP activated the Nrf2 pathway and inhibited NLRP3 signaling to significantly reduce the levels of inflammatory cytokines IL-1β, IL-6, and TNF-α. Conclusions: Our results indicate that compound PSCP has the potential to prevent or control chronic kidney damage.